The anisotropic quantum Rabi model with diamagnetic term - Anaya-Contreras, Jorge A.; Ramos-Prieto, Irán; Zúñiga-Segundo, Arturo; Moya-Cessa, Héctor M. (Frontiers in Physics, 2025)
We employ a squeeze operator transformation approach to solve the anisotropic quantum Rabi model that includes a diamagnetic term. By carefully adjusting the amplitude of the diamagnetic term, we demonstrate that the anisotropic Rabi model with the A2 term can be exactly reduced to either a Jaynes-Cummings or an anti-Jaynes-Cummings model without requiring any approximations.